Pengembangan E-LKPD Berbasis Contextual Teaching and Learning (CTL) pada Materi Struktur Atom Fase E SMA/MA - Putri, Yolanda; Andromeda, Andromeda (Lembaga Yasin AlSys, 2026)
The development of digital teaching materials has become an essential requirement in the implementation of Kurikulum Merdeka, particularly for abstract chemistry topics such as atomic structure, yet systematically designed electronic student worksheet (E-LKPD) products based on the Contextual Teaching and Learning (CTL) approach and validated through rigorous procedures remain relatively limited. This study aimed to develop a CTL-based E-LKPD on atomic structure material for Phase E at the senior high school/Islamic senior high school (SMA/MA) level and to assess the feasibility of the product through validity testing. The study employed a research and development approach within the framework of Educational Design Research (EDR) using the Plomp development model, which comprises the preliminary research phase (needs analysis through teacher interviews and student questionnaires, literature review, and conceptual framework development) and the development/prototyping phase up to Prototype III. Data were obtained from validation questionnaires assessing the content, presentation, language, and graphical components, completed by five validators consisting of chemistry lecturers and chemistry teachers. Validation data were analyzed using Aiken’s V index. The results showed an average Aiken’s V value of 0.85, categorized as valid across all assessed aspects, accompanied by recommendations for improvement that were used to revise the product until Prototype III was obtained. These findings indicate that the developed CTL-based E-LKPD is suitable for use as a supplementary teaching material to help students understand atomic structure concepts in a more contextual and engaging manner, while further studies are recommended to examine its practicality and effectiveness in real classroom learning contexts.